Regional security and cooperation in the Arctic and Baltic: destabilisation follows Ukraine crisis - Etzold, Tobias; Steinicke, Stefan (DEU, 2015)
The Ukraine conflict has created a deep and long-running crisis of confidence in relations between the West and Russia, as Moscow challenges the foundations of the European security order. Russia's behaviour in the Baltic and Arctic regions, which it shares with members of NATO and the European Union, has become increasingly confrontative and presents an impediment to regional cooperation and security. While growing instability looms over these two regions, all the states there should maintain at least low-level regional cooperation with Russia, in order to prevent any further escalation of security tensions and at least partially restore trust. (author's abstract)